If be the ratio of the roots of the quadratic equation in x, 3m^{2}x^{2}+m(m – 4 )x+2 = 0, then the least value of m for which + = 1, is :

a. |
2 – |
b. |
4 – 3 |

c. |
− 2 + |
d. |
4 – 2 |

If be the ratio of the roots of the quadratic equation in x, 3m^{2}x^{2}+m(m – 4 )x+2 = 0, then the least value of m for which + = 1, is :

a. |
2 – |
b. |
4 – 3 |

c. |
− 2 + |
d. |
4 – 2 |

1 Answer

127 votes

3m^{2}x^{2} + m(m – 4) x + 2 = 0

+ = 1, + = 1, =

= 3

**= ** ** , ** ** = **

(m – 4 )^{2} = 18, m = 4 , 4

127 votes

127